1977
DOI: 10.1007/bf00927976
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus, a key to life on the primitive earth

Abstract: The phosphorus of the primitive Earth was present as phosphates. It is strongly probably that a portion of the phosphate was present as condensed phosphates. The primitive Earth was highly deficient in the total available phosphorus until a sufficient quantity of phosphorus weathered from the igneous rocks in which it was entrapped. Approximately three billion years were required for the seas to become saturated. Until this time passed the seas acted as a giant sink for phosphorus, diluting it to the extent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Similarly, a suite of other phosphonic acids has been synthesized via ultraviolet irradiation of phosphite in the presence of formaldehyde or simple alcohols (De Graaf et al 1995). Yamagata et al (1991) reported the detection of condensed phosphates (primarily pyrophosphate and tripolyphosphate) in condensates from experiments in which apatite mixed with basalt had been subjected to elevated temperature, thus indirectly confirming an earlier prediction that P 4 O 10 would be volatilized from apatite at high temperature (Griffith et al 1977). More striking was the identification of the same products in condensates collected from a fumarole of the volcano Mount Usu.…”
Section: Lightning In Volcanic Eruption Clouds and Phosphatementioning
confidence: 80%
“…Similarly, a suite of other phosphonic acids has been synthesized via ultraviolet irradiation of phosphite in the presence of formaldehyde or simple alcohols (De Graaf et al 1995). Yamagata et al (1991) reported the detection of condensed phosphates (primarily pyrophosphate and tripolyphosphate) in condensates from experiments in which apatite mixed with basalt had been subjected to elevated temperature, thus indirectly confirming an earlier prediction that P 4 O 10 would be volatilized from apatite at high temperature (Griffith et al 1977). More striking was the identification of the same products in condensates collected from a fumarole of the volcano Mount Usu.…”
Section: Lightning In Volcanic Eruption Clouds and Phosphatementioning
confidence: 80%
“…Although previous research on P weathering has focused on volcanic rocks, sedimentary rocks contain the largest reservoir of C and P on the Earth's surface [ Griffith et al , 1977; Hunt , 1972], and they are also subjected to chemical weathering. Black shales are organic‐rich sedimentary rocks formed by sediment deposition under low oxygen or anoxic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A possibility of the formation of tetrametaphosphate (TetMP) via a P4010 molecule on the primitive earth through volcanic activity was proposed by Griffith (1977) and Griffith et al (1977), and recently Yamagata et al (1982) demonstrated that TetMP was an effective reagent for the phosphorylation of adenosine. Trimetaphosphate (TriMP), having a cyclic structure similar to TetMP, was also likely to have been supplied on the primitive earth (Osterberg and Orgel, 1972).…”
Section: Introductionmentioning
confidence: 99%